VD_FINDINFO HC / 2024 / 825 vom 8. November 2024 - VD Tribunal cantonal (2024)
CAS CLAIR, EXPULSION DE LOCATAIRE | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 254 al. 1 CPC, 257 al. 1 CPC (CH), 257 CPC (CH), 312 al. 1 CPC (CH)